URGENSI PELIBATAN DAN PARTISIPASI PEMUDA DALAM UPAYA PENGEMBANGAN PARIWISATA TAMAN WISATA ALAM SIBOLANGIT - M. Ainur Ridlo (Lembaga Pengembangan Kinerja Dosen, 2023)
The existence of tourism in Indonesia is one of the main attractions for tourists to visit Indonesia to enjoy the natural beauty of Indonesia's earth. In Indonesia there are many tourist objects that have high selling power besides Borobudur, there is also the Sibolangit nature tourism in, North Sumatra, which is also the focus of the study being studied by researchers. Efforts to build tourism are certainly not only the duty and responsibility of the government, but local governments, village governments, local communities and youth youth organizations must have a high sense of concern and empathy for the existence and development of tourism above. The results in this study indicate that the existence of youth has a very strategic role in the progress or not of a tourist attraction, because youth plays a role in terms of marketing with their abilities and skills in using social media so that the existence of tourist objects becomes increasingly known by many people, especially foreign tourists. The two youths can also be a bastion of security and comfort for visitors and thirdly the involvement of youth in building and developing tourism is also a positive value from an economic perspective which leads to the welfare of the surrounding community. So in a simple conclusion, youth must be involved and involved in the development and construction of tourist objects, especially in Sibolangit tourism in Deli Serdang, North Sumatra.